Developing User-Friendly and Cost-Effective Sales Accounting Systems for the MSME Sector - Sitorus, Destri Sambara (Journal of Economics Education and Entrepreneurship, 2024)
This study aimed to develop and implement a user-friendly sales accounting information system for Manja Cheese Tea Macanan, a Small and Medium-sized Enterprise (SME) specializing in contemporary milk-based beverages. Employing a development research methodology, data was collected through interviews, observations, and document analysis to understand the existing sale process and information needs of Manja Cheese Tea Macanan. The sales accounting information system design process comprised constructing relational database tables, defining entity-relationship diagrams, creating data retrieval queries, and designing user-friendly forms, reports, and navigation menus (login, home, sales switchboard). The findings revealed that Manja Cheese Tea Macanan relied on a amnual sales system, highlighting the need for automation and improved data management. The designed sales accounting information system was tailored to the specific needs of Manja Cheese Tea Macanan and successfully implemented. The system demonstrated operational effectiveness in facilitating sales recording, data management, and information retrieval, addresing the identified limitations of the earlier manual system.